Effectiveness of the community paramedicine at home (CP@home) program for frequent users of emergency medical services in Ontario: a randomized controlled trial - Gina Agarwal; Ricardo Angeles; Jasdeep Brar; Melissa Pirrie; Francine Marzanek; Brent McLeod; Lehana Thabane (BMC, 2024)
Abstract Objective To evaluate the impact of the Community Paramedicine at Home (CP@home) program, a community paramedicine home-visit intervention, on reducing emergency medical services (EMS) calls among frequent users. Design A 6-month, open-label, pragmatic, randomized controlled trial with parallel intervention and control arms. An online automated platform (randomizer.org) was used to randomly allocate participants using a 1:1 allocation sequence. Setting In homes of frequent EMS users in four paramedic services and regions across Ontario, Canada. Participants Eligible participants were frequent callers (≥ 3 EMS calls within six months and ≥ 1 EMS call within the previous month), or had ≥ 1 lift assist call within the previous month, or were referred by paramedics. Intervention Community paramedics conducted risk assessments, provided health education, referred appropriate resources, and reported to family physicians for up to three home visits. The control arm received usual care. Primary outcome measure EMS calls in 6 months during intervention. Results Two thousand two hundred eighty four eligible participants were randomly allocated to the intervention and control groups, with 265 participants lost to follow-up due to inability to retrieve participant records from EMS databases. There were 1025 intervention participants (52.7% female, mean age 69.65 years [standard deviation (SD) = 19.98]) and 994 control participants (52.0% female, mean age 69.78 years [SD = 19.09]). In the post-intervention intention-to-treat analysis (zero-inflated negative binomial regression), the EMS call rate was not significantly lower in the intervention group compared to the control group (incidence rate ratio [IRR] = 0.88, 95% confidence interval [CI]: 0.76, 1.01). In the subgroup analysis, the intervention had a significant effect in the lift assist caller subgroup (IRR = 0.73, 95% CI: 0.58, 0.92), but no significant effect among the frequent caller subgroup (IRR = 0.97, 95% CI: 0.82, 1.14). The sensitivity analyses found a similar association for the lift assist caller subgroup. There was a significant subgroup effect (p-value for interaction < 0.01). Conclusions CP@home had a significant impact on reducing EMS calls for those with a lift assist call but not for the overall sample. This program filled a healthcare gap by shifting primary care delivery, which could reduce the disproportionate number of EMS calls, thus reducing healthcare costs. Trial registration Registered with ClinicalTrials.gov NCT02835989 on July 14, 2016.